Word priming in schizophrenia: Associational and semantic influences - Nestor, Paul G. (2005)
We examined semantic vs. associational influences on word priming in schizophrenia. Tested on three occasions, subjects made speeded lexical decisions to three kinds of prime-word relationships: semantic-only (e.g., Deer-Pony), associated-only (e.g., Bee-Honey), or semantic-and-associated (e.g., Doctor-Nurse). Controls showed greater priming of words related via two relationships (semantic-and-associated) than for words related only semantically.. However, patients showed greater priming for associated-only words than for words related only semantically. Schizophrenic patients may show an associational bias, restricting semantic integration and contributing to their disturbed thinking.